A Contextual Approach to Contemporary Da'wah: Bridging Legal Education and Mathematics-Based Curriculum Development - Nurhikmah; Ibnu Imam Al Ayyubi; Namiyah Fitriani; Ari Limay Trisno Putra; M. Baihaki Hidayatullah (Badan usaha Milik Desa Berkaho Pungpungan, 2025)
This study aims to examine the implementation of the contextual approach in the development of contemporary Islamic da'wah through legal education and the development of a mathematics education-based curriculum tailored to the needs of modern youth. Qualitative research methods were employed, using in-depth interviews, direct observation, and document analysis for data collection. The contextual approach was chosen for its ability to integrate Islamic values with legal principles and mathematical concepts such as patterns, logic, and regularity, so that da'wah becomes not only a spiritual tool but also an intellectual tool. Data were analyzed using thematic analysis to identify key themes relating to strategies, opportunities and challenges in applying this approach. The findings show that the application of the contextual approach to math-based da'wah in legal education enhances students' logical and practical understanding of Islamic values and legal principles. However, challenges faced such as limited teacher competence in integrating these areas and lack of relevant teaching materials were identified. This research provides practical recommendations for preachers, educators, and policy makers to support innovative, relevant, and sustainable da'wah strategies. Therefore, this research contributes to the development of effective da'wah methods.